Analysis of kinematics characteristics on the backhand twist technique for China elite male hand-shake table tennis players - Zhang, X. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
Research Objective: The backhand twist technique of Zhang Jike and Fan Zhendong is the best and most reasonable in China national table tennis team. The other players with hand-shake should learn from them. The paper gave a 3-D kinematic test and analysis on the backhand twist technique of Zhang Jike and Fan Zhendong to reveal the kinematics characteristics and action technique principle of male hand-shake table tennis players, which would lay the foundation of technical movement monitoring and diagnosis system for the excellent table tennis athletes in our country for the future. Research methods: The backhand twist techniques of Zhang Jike and Fan Zhendong were recorded synchronously by two high-speed cameras (100 frames per second) on three-dimension in Xiamen closed training base for national team, at April of 2014. During the test, the head coach of China Table Tennis Team serve multi ball to the short table of the backhand, the two players twisted the ball in diagonal with maximum force. At least 10 times techniques of each athlete were collected. Used by Simi Motion movement technical analysis software to analyse the data. Research results and conclusion: (1) During the stage of racket backward, the wrist and trunk of Zhang Jike and Fan Zhendong turned round fully. Fan Zhendong`s torsional amplitude of the wrist was about 270 degree, and that of Zhang Jike was about 180 degrees. (2) During the hitting stage, right shoulders of two athletes were higher than the left shoulder. Right shoulder forced forward and gave the forearm and wrist with a stable support. The forward force was bigger than the right force. The center of the body weight pressed forward. (3) The average time of Zhang Jike from the coming ball rebounded the table to hit the ball was 0.215 seconds, and that of Fan Zhendong was 0.213 seconds, (4) Two athletes had a solid, focused power and a fast speed for swing of the racket at the moment of hitting the ball.